Estudo dos fatores de risco maternos associados à sepse neonatal precoce em hospital terciário da Amazônia brasileira Study of maternal risk factors associated with early-onset neonatal sepsis in a tertiary hospital of the Brazilian Amazonia - Rossiclei de Souza Pinheiro; Luiz Carlos de Lima Ferreira; Ione Rodrigues Brum; Jefferson Pereira Guilherme; Rossicléa Lins Monte (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2007)
OBJETIVO: identificar os fatores de risco maternos envolvidos na sepse neonatal precoce, pesquisando vaginose bacteriana, microorganismos isolados em cultura de urina materna e na hemocultura do recém-nascido na sala de parto. MÉTODOS: estudo de coorte longitudinal prospectivo, envolvendo, aleatoriamente, 302 mães e seus recém-nascidos, que foram acompanhados até sete dias de vida, a fim de diagnosticar sepse. RESULTADOS: diagnosticados 16 casos (5,3%) de sepse neonatal precoce. O número médio de consultas no pré-natal foi 5,2 (DP=1,8). Das 269 (89,1%) grávidas que fizeram acompanhamento pré-natal, porém, 117 (43,4%) fizeram mais de seis consultas; 90 (29,8%) tiveram bolsa rota antes do parto, somente 22 (7,3%) tinham mais de 18 horas. Cento e vinte e três grávidas (40,7%) queixavam-se de corrimento vaginal, entretanto 47 (15,6%) tinham vaginose bacteriana. Em 23 (7,6%), foi identificada bacteriúria; duas (0,7%) apresentavam febre no domicílio e 122 (40,4%) fizeram antibioticoprofilaxia intraparto. Quarenta recém-nascidos (13,2%) foram prematuros, 37 (12,3%) com baixo peso. A avaliação do risco relativo mostrou significância para prematuridade (RR=92,9; IC95%=12,6-684,7), número de consultas no pré-natal inferior a seis (RR=10,8; IC95%=1,4-80,8), febre no domicílio (RR=10,0; IC95%=2,3-43,5), baixo peso ao nascer (RR=21,5; IC95%=7,3-63,2) e Apgar inferior a sete no quinto minuto (RR=19,5; IC95%=9,0-41,9). Foram encontradas diferenças significantes no nível de 5% na comparação das médias para o baixo número de consultas no pré-natal, prematuridade e baixo peso ao nascer. CONCLUSÕES: o principal microorganismo isolado na hemocultura dos recém-nascidos foi o Streptococcus agalactiae. Prematuridade, ausência de seguimento pré-natal e baixo peso ao nascer foram os fatores de risco mais associados com sepse neonatal precoce. PURPOSE: to identify the main maternal risk factors involved in early-onset neonatal sepsis, evaluating the risk associations between bacterial vaginosis and isolated microorganisms found in the maternal urine culture and in the newborn blood culture in the delivery room. METHODS: randomized longitudinal cohort study involving 302 mothers and their newborns. All neonates were followed up for seven days in order to diagnose sepsis. RESULTS: the outcomes were the following: 16 (5.3%) early-onset neonatal sepsis cases (incidence of 53 cases per 1,000 live births). The average number of prenatal appointments with a doctor was 5.2 (SD=1.8). The number of women with prenatal follow-up was 269 (89.1%), but only 117 (43.4%) of them went to six or more medical appointments, 90 (29.8%) had premature rupture of membranes before delivery, but only 22 (7.3%) had it for more than 18 hours. A total of 123 women (40.7%) complained of vaginal discharge, but only 47 (15.6%) of them had bacterial vaginosis, 92 (30.4%) complained of urinary infection, but only 23 (7.6%) of them had bacteriuria, two (0.7%) had fever at home, 122 (40.4%) received intra-partum antibiotic prophylaxis, 40 (13.2%) had premature delivery and 37 (12.3%) had low-birth-weight babies. Gestational age was a significant risk factor (RR=92.9; IC95%:12.6-684.7), as well as the number of prenatal appointments (RR=10,8; IC95%:1,4-80,8), fever (RR=10,0; IC95%:2,3-43,5), low-birth-weight (RR=21,5; IC95%:7,3-63,2) and early neonatal death (RR=89,4; IC95%:11,16-720,6). A significant difference of 5% was found in the comparison of the averages of lower number of prenatal appointments, prematurity and lower birth weight. CONCLUSIONS: the major microorganism isolated in the newborns' blood culture was the Streptococcus agalactiae. Prematurity, lack of prenatal follow up and low birth weight were the risk factors more associated with early neonatal sepsis.